SINTESIS ASAM SINAMAT DARI BENZALDEHIDA DAN ASAM MALONAT DENGAN KATALIS DIETILAMINA - Jeffry Julianus; Elvan Luckyvano (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Cinnamic acid is a natural compound that has known had activities as: antimicrobia; flavour in food; soap; cosmetic; and inhibitor proliferation of caco-2 cells. Cinammic acid compound commonly got by isolated kayu manis bark with yield 2.2%. There was a limitation amount of cinnamic acid that got by isolation so needed another effort to get much amount of cinnamic acid. There was an effort to get much amount of cinnamic acid that was by synthesized it. Synthesis process was carried out by reacted benzaldehyde 45 mmol (4.9 g) and malonic acid 45 mmol (4.5 ml) with catalyzed dietylamina for 7.5 hours at 80OC. Synthetic compound was carried out organoleptic test, solubility test, melting point test, gas chromatography, structure elucidation with ultraviolet spectrophotometry, infrared spectrophotometry, nuclear magnetic resonance spectroscopy (1H-NMR), mass spectroscopy; and amount of yield. Synthetic compound was white smooth crystal powder, and had a specific flavour with yield was4.68% and melting point was 132-133OC. Solubility test showed the synthetic compound dissolved in ethanol, methanol, chloroform, dimethyl sulfoxide, hot water, and acetone; very difficult soluble in water. Gas chromatography chromatogram showed one peak with retention time 13.321 minute. Based on structure elucidation conclude that synthetic compound was cinnamic acid.